"I Depend on Her for Everything": A Retrospective Chart Review of Home Care Worker Service Disruptions for Homebound Older Adults During the COVID-19 Pandemic. (April 2023) - Xu, Emily L.; Kim, Patricia S.; Yee, Cynthia; Zhang, Meng; Reckrey, Jennifer M.; Lubetsky, Sara; Zhao, Duzhi; Ornstein, Katherine A.; Franzosa, Emily
Home care workers played critical roles in meeting the complex medical and social needs of homebound adults during COVID-19, yet their contributions remain underappreciated. This study characterizes home care workers' roles during COVID-19 and examines how home care disruptions impacted homebound individuals and caregivers. Using a qualitative analysis of electronic medical records among a randomly sampled subset of homebound patients in a home-based primary care practice, we found that home care workers were essential in meeting existing and new needs of homebound individuals. Insufficient home care worker services, including unstable schedules and inadequate hours of paid care, became particularly disruptive, leading to risks for patients and their caregivers. Given their integral role on care teams, home care workers must be a policy focus to prepare for emergent situations and ensure that homebound individuals have access to high quality, stable home care.